2016
DOI: 10.1039/c5dt02747k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a novel nanocomposite NaLuF4:Gd,Yb,Tm@SiO2@Ag@TiO2 with high photocatalytic activity driven by simulated solar light

Abstract: A novel nanocomposite photocatalyst NaLuF4:Gd,Yb,Tm@SiO2@Ag@TiO2 was developed for the first time. This composite material has a sandwich structure, including a NaLuF4:Gd,Yb,Tm upconversion nanocrystals (UCNCs) core, a media shell of amorphous SiO2 decorated with Ag nanoparticles, and an outer shell of anatase TiO2. The designed new structure takes advantage of the synergetic effect of UCNCs, Ag nanoparticles and TiO2. The UCNCs absorb near-infrared (NIR) light and transfer energy to TiO2, which extends the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…1h ). The determined values of interplanar distances between adjacent lattice fringes are 0.50 and 0.224 nm, corresponding to (100) and (111) crystal planes of UCNPs and Ag nanoparticles, 27 respectively. The measured lattice space (0.50 nm) of UCNPs in UCNPs@SiO 2 @Ag, corresponding to the (100) hexagonal phase crystal plane of UCNPs, demonstrates that the hexagonal phase structure of UCNPs remains unchanged after forming UCNPs@SiO 2 @Ag nanoparticles.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…1h ). The determined values of interplanar distances between adjacent lattice fringes are 0.50 and 0.224 nm, corresponding to (100) and (111) crystal planes of UCNPs and Ag nanoparticles, 27 respectively. The measured lattice space (0.50 nm) of UCNPs in UCNPs@SiO 2 @Ag, corresponding to the (100) hexagonal phase crystal plane of UCNPs, demonstrates that the hexagonal phase structure of UCNPs remains unchanged after forming UCNPs@SiO 2 @Ag nanoparticles.…”
Section: Resultsmentioning
confidence: 96%
“…39,60 Notably, the photocatalytic degradation activity of the as-prepared nanocomposite is also higher than the various UCNPs-modied photocatalysts reported previously (Table S1 in ESI †). 25,27,28 Considering that the amount of Ag loading may be an important factor in the photocatalysis, the dependence of the degradation efficiency of RhB on the amount of Ag loading (0-10 wt%) was studied further. As shown in Fig.…”
Section: Photocatalytic Degradation Of Rhbmentioning
confidence: 99%
See 2 more Smart Citations
“…That results increment in fluorescence intensity directly associated with enhanced decay rates. [29][30][31] Wang et al fabricated truncated triangular silver nanoprisms and made a theoretical as well as experimental investigation about the influence of these nanoprisms on the fluorescence property of europium complex Eu(TTFA) 3 . 32 They found that the emission intensity of Eu 3+ in the complex is greatly enhanced through minimization of the nonradiative decay losses.…”
Section: Introductionmentioning
confidence: 99%